2019
DOI: 10.3390/ijms20092163
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrocannabinol Reduces Hapten-Driven Mast Cell Accumulation and Persistent Tactile Sensitivity in Mouse Model of Allergen-Provoked Localized Vulvodynia

Abstract: Vulvodynia is a remarkably prevalent chronic pain condition of unknown etiology. An increase in numbers of vulvar mast cells often accompanies a clinical diagnosis of vulvodynia and a history of allergies amplifies the risk of developing this condition. We previously showed that repeated exposures to oxazolone dissolved in ethanol on the labiar skin of mice led to persistent genital sensitivity to pressure and a sustained increase in labiar mast cells. Here we sensitized female mice to the hapten dinitrofluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…Vulvar biopsies from diagnosed patients show increases in mast cells and nerves [4,5,6]. To recapitulate and dissect the pathobiology of allergy-driven tactile sensitivity and to inform novel therapies, we established mouse models of allergy-driven genital pain [7,8,9]. We have shown that contact hypersensitivity to the commonly used laboratory haptens oxazolone (Ox) on the labiar skin or dinitrofluorobenzene (DNFB) on the labiar skin or vaginal canal induces persistent tactile genital pain and increased accumulation of mast cells in the labiar tissues of outbred, female ND4 mice well beyond the resolution of visible inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Vulvar biopsies from diagnosed patients show increases in mast cells and nerves [4,5,6]. To recapitulate and dissect the pathobiology of allergy-driven tactile sensitivity and to inform novel therapies, we established mouse models of allergy-driven genital pain [7,8,9]. We have shown that contact hypersensitivity to the commonly used laboratory haptens oxazolone (Ox) on the labiar skin or dinitrofluorobenzene (DNFB) on the labiar skin or vaginal canal induces persistent tactile genital pain and increased accumulation of mast cells in the labiar tissues of outbred, female ND4 mice well beyond the resolution of visible inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Boo and collaborators present original results in a mouse model of allergen-provoked localized vulvodynia, supporting the hypothesis that mast cells are involved in this painful disorder [113].…”
mentioning
confidence: 68%
“…Tissue levels of Cxcl2, IL-1β and IL-6 were evaluated as previously described [ 20 , 21 ], from whole cell lysates using cytokine specific duo-set ELISA kits (R&D Systems, Minneapolis, MN, USA). Total serum Immunoglobulin E (IgE) content was measured by ELISA (Bethyl Laboratories, Montogomery, TX, USA) in serum isolated from blood collected either from the sub-manibular vein or by post-mortem heart puncture.…”
Section: Methodsmentioning
confidence: 99%
“…EPO and MPO analyses were performed as previously described [ 21 ]. For EPO measurements, labiar samples that had been stored for at least 24 hours in 0.5% HTAB buffer were thawed and 4x the original amount of HTAB buffer was added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation